Sex determination in bees. XXX. Effects of juvenile hormone on the development of tergal glands in Melipona - Bonetti, Ana Maria; da Cruz-Landim, Carminda [UNESP]; Kerr, Warwick Estevam (Taylor & Francis, 1994)
Worker larvae of Melipona rufiventris, M. quadrifasciata and M. compressipes were treated topically with juvenile hormone (JH) during the cocoon-spinning phase. Examination of the tergites of the queens obtained following JH application showed induced differentiation into adults with full female (queen) traits. Melipona workers had tergal glands only in tergite II, whereas natural and JH-induced queens had tergal glands in tergite II plus additional glands in at least one other of tergites III to VII. © 1994 International Bee Research Association.
Keywords: Castes; Differentiation; Females; Genetic expression; Juvenile hormone; Melipona; Stingless bees; Tergal glands